Literasi Sains Modern Dalam Isu Sosiosaintifik Berbasis Konteks Lokal: Sebuah Tinjauan Pustaka Sistematis Untuk Pembelajaran Interdisipliner Fisika Dan Matematika - Purwanto, Andik; Putri, Prismadian A (Kumparan Fisika, 2025)
Twenty-first-century science education necessitates a paradigm shift from mere conceptual mastery towards functional scientific literacy, defined as the ability to utilize scientific knowledge for decision-making on complex societal issues. However, physics instruction often remains decontextualized and theoretical, consequently failing to equip students with this crucial competence. This research aims to conduct a Systematic Literature Review (SLR) to map and synthesize theoretical frameworks concerning the integration of locally-contextualized Socioscientific Issues (SSI) to strengthen modern scientific literacy. Through searches in the Google Scholar and Scopus databases, applying strict inclusion and exclusion criteria, twenty-five relevant articles were thematically analyzed. The synthesis yielded three principal themes: (1) The fundamental role of SSI as a bridge between science concepts and ethical reasoning and decision-making; (2) The criticality of local context in enhancing the relevance, engagement, and meaningfulness of science learning; (3) The potential synergy between physics and mathematics disciplines in facilitating quantitative analysis and modeling of SSI. This review concludes that a physics learning approach integrating SSI, local context, and mathematical reasoning represents a promising framework for realizing the goals of modern scientific literacy in Indonesia. The implication of this study is the urgent need for the development of physics instructional models and materials that explicitly adopt this proposed framework.